Coolest Student Papers at Finland Futures Research Centre 2023–2024 : Tulevaisuuden tutkimuskeskuksen valittuja opiskelijatöitä 2023–2024 - Aalto, Hanna-Kaisa; Ferreira-Aulu, Marianna Birmoser; Halme, Amanda; Heikkilä, Katariina; Heino, Hanna; Keski-Pukkila, Pasi; Parkkinen, Marjukka; Puustinen, Sari; Richards, Martyn; Salminen, Hazel; Shaw, Morgan; Siivonen, Katriina; et al. (Turun yliopisto, 2025)
Finland Futures Research Centre (FFRC) has published since 2016 a collection of most prominent student papers written during the previous study year. The FFRC wants to offer a real publication forum for students and help them to get perhaps the first publication marking on their list of publications. Even if it sometimes feels that the role of academic writing is diminishing in communicating the results and developments of sciences, it is still a skill needed in the future. Artificial intelligence apps also need information to gather and process. Let this publication be also part of this new purpose.
Our publication consists of writings of students from our Master’s Degree Program in Futures Studies, Sustainable Development Studies of University of Turku and Finland Futures Academy. Because student papers are originally written in Finnish or English we publish them in their original language. This time the papers deal with questions of current challenges like sustainability and cultural sustainability, futures of public health care; and basic scientific questions like methodological development of futures studies and foresight as well as history of science. The students have been eager to participate in choosing the topics of writings in different courses which shows that they are interested in global challenges and the role of science in solving these.
We hope that the publication in hand gives courage to the authors to continue on the path of academic writing, works as an example for other students and gives fruits of thought to other readers and users of information – whether they are humans or machines.